Irrational beliefs in relation to certain behaviors in adolescents. (European Journal of Education and Psychology, 2010)
This research is part of a cognitive frame. Consider also the physiological component of the conduct, whether as part of the same or as a possible remote cause, especially in certain pathologies. Being analyzed the impact of irrational beliefs and acceptance to see their relationship with the previous irrational beliefs and the impact of both in the following areas: consumption of psychoactive substances and environmental awareness in youth. In turn, environmental awareness is included for the importance of behavior in favor of ecology that promotes that are necessary today in both youth and adults for self-sustainability of the planet. This work constitutes a contribution in the search for psychological deficits and emotional needs of adolescents. Any positive result in this line will be considered as a demand for attention and specific training in this area that young people claim their right to receive comprehensive and quality education. Would be necessary to help new generations to build freely existential project that his life acquired a new meaning.